Structural characteristics of television news commentary as a genre in the context of media convergence - Yuxi, Chen (Journal of the Belarusian State University. Journalism, 2026)
This article analyses the multimedia programme «Host commentary: Xinwen Lianbo». Drawing on T. А. van Dijk’s theory of news analysis, a discourse analysis of the programme, including its narrative structure, is conducted. It explores how the genre of news commentary is transformed through systematised textual rules. The analysis reveals that, at the structural level, the programme has developed a stable news schema headline – introduction – event – verbal reaction – commentary. It is concluded that programme «Host commentary: Xinwen Lianbo» transforms the traditional genre of news commentary through the introduction of structural innovations, providing a clear practical example for reforming traditional news commentary programmes in Belarus.
Keywords: television news commentary; news discourse analysis; genre studies; media convergence; «Host commentary: Xinwen Lianbo»